WUJUD PRAGMATIK IMPERATIF DALAM CERAMAH USTADZ FELIX SIAUW PADA YOUTUBE UNGGAHAN BULAN APRIL 2023 - Lalu Mas'ud; Utia; Eva Nurmayani; Muhammad Khairul Abror (Universitas Hamzanwadi, 2026)
This study aims to describe and explain the forms of imperative pragmatics used in Ustadz Felix Siauw's lectures on YouTube. The method used was descriptive qualitative. Data were collected using listening and note-taking techniques. The results showed the use of seven types of imperative pragmatics in Ustadz Felix's lectures: (1) utterances with the imperative pragmatic meaning of commands; (2) utterances with the imperative pragmatic meaning of commands; (3) utterances with the imperative pragmatic meaning of requests; (4) utterances with the imperative pragmatic meaning of urges; (5) utterances with the imperative pragmatic meaning of prohibitions; (6) utterances with the imperative pragmatic meaning of urges; and (7) utterances with the imperative pragmatic meaning of hopes.